Pressure fluctuation characteristics in the sidewall gaps of a centrifugal dredging pump. Issue 4 (12th June 2017) - Cao, Lei; Xiao, Yexiang; Wang, Zhengwei; Luo, Yongyao; Zhao, Xiaoran
Abstract : Purpose: The purpose of this paper is to study the pressure fluctuation characteristics in the sidewall gaps of a centrifugal dredging pump in detail and discover the excitation sources. Design/methodology/approach: An unsteady numerical simulation with shear–stress transport–scale-adaptive simulation (SAS-SST) model was conducted for a centrifugal pump considering the sidewall gaps. The numerical codes were validated by a model test carried out in China Water Resources Beifang Investigation, Design and Research Co., Ltd. Fast Fourier transform was used to obtain the frequency components of the pressure fluctuation. Findings: Pressure fluctuation characteristics inside the pump were analyzed for a condition near the design point. In the sidewall gaps, the circumferential, radial and axial distribution of the pressure fluctuation amplitude follow different laws. The non-axisymmetrical distribution of pressure fluctuation in the sidewall gaps shows that the unsteady flow in the volute casing which has a non-axisymmetrical geometry imposes an evident effect on the flow field in the sidewall gaps and the interaction between the main flow and the clearance flow cannot be neglected. There are several frequency components appearing as the dominant frequencies at different locations in the sidewall gaps, but the relatively stronger pressure fluctuations are all dominated by the rotating frequency. It indicates that the rotating impeller, which originally makes the shrouds rotate, is the primarily excitation source of the pressure fluctuations in the sidewall gaps. Originality/value: The pressure fluctuation characteristics in the sidewall gaps of centrifugal pumps were first comprehensively analyzed. Unsteady flows in the sidewall gaps should be considered during the design and operation of centrifugal pumps.